STRATEGI PENGEMBANGAN EKOWISATA DI KAWASAN HUTAN MOKWAM-PEGUNUNGAN ARFAK, PROVINSI PAPUA BARAT - Fatem, Sepus; Susanti, Ika; Siburian, Rima HS.; Morin, Henderina; Erari, Semuel S. (Median : Jurnal Ilmu Ilmu Eksakta, 2024)
The Mokwam forest is included in the territory of the Warmare District as a potential ecotourism area that has endemic animals, plants /flora, bird watching, Good bird attraction, mountain landscape, Moss forest, And the cave as a tourist attraction. The aim of the research is to determine the potentential of ecotourism in the forest area of Mokwam based on natural reources and strategies for this purpose, direction and tourism development policy mokwam forest area because of tourists visit special interest or foreign nusantara in continu. Which affects the economic movement of local people. The result of SWOT which is used by researchers can be described that a lot of factors affect the development of Forest Mokwam Ecotourism. The result showed that the key to the success of First of strength with value is 0.741, the second is 0.727, and the third is 0.709. The first weakness factor value is 0,323, the second is 0,192 and the third is 0,528. In external factor show that the first of the Key Factor Success (KFS) from Opportunity Factor value is 0.528, the second is 0.517 and the third is 0.516. In Threat Factor showed that the first value is 0.249, the second is 0.246 and the third is 0.246. The result of this research determined that the Mokwam Forest is suitable to develop the ecotourism area based on the environmental factor. It could be implemented based on the guidelines from Legacy Number. 41/1999 and the Legal of Government Number 34/2002 with management status is Limited Used of Forest Sanctuary in Area Used, and Environmental Services Used and pemanfaatan kawasan, pemanfaatan jasa lingkungan, and Forest Collecting no wood.